If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -16 = 4x + -3 Reorder the terms: -16 + 2x = 4x + -3 Reorder the terms: -16 + 2x = -3 + 4x Solving -16 + 2x = -3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -16 + 2x + -4x = -3 + 4x + -4x Combine like terms: 2x + -4x = -2x -16 + -2x = -3 + 4x + -4x Combine like terms: 4x + -4x = 0 -16 + -2x = -3 + 0 -16 + -2x = -3 Add '16' to each side of the equation. -16 + 16 + -2x = -3 + 16 Combine like terms: -16 + 16 = 0 0 + -2x = -3 + 16 -2x = -3 + 16 Combine like terms: -3 + 16 = 13 -2x = 13 Divide each side by '-2'. x = -6.5 Simplifying x = -6.5
| y=3+6 | | r-(34)=18 | | (5x-3)(2x+11)= | | -9+5=x | | -9+5= | | m-9=54 | | p^2+2pq+.36=1 | | 9x^2+4= | | -8w=48 | | [5-3x]=1 | | g-4=18 | | 13n-16n=18 | | 4(7)+7y=56 | | 32-18x+x^2=0 | | 2x=6x+12 | | 4x+7(0)=56 | | 3w^4+18w^3-24w^2= | | 6x-3(y-7x)+2(5x-y)= | | 7p-11p+3=3-4p | | 4(0)+7y=56 | | 9+=4t+120 | | 10c+9+c^2=0 | | 6y-9=4y+2y-16 | | y^3+2y^2-25y-50=0 | | y^3+2y^2=25y+50 | | 12n+2=46 | | 27x^3-45x^2-147x+245= | | .548= | | -4.8+b+.6=1.8+3.6b | | x+(3(x-2)-3)=2-(3-x) | | 7d-4=17 | | 27x-45x-147x+245= |